Treatment of perianal fistula in Crohn's disease: a systematic review and meta‐analysis comparing seton drainage and anti‐tumour necrosis factor treatment. (4th July 2016) - de Groof, E. J.; Sahami, S.; Lucas, C.; Ponsioen, C. Y.; Bemelman, W. A.; Buskens, C. J.
Abstract: Aim: The introduction of anti‐tumour necrosis factor (anti‐TNF; infliximab and adalimumab) has changed the management of Crohn's perianal fistula from almost exclusively surgical treatment to one with a much larger emphasis on medical therapy. The aim of this systematic review was to provide an overview of the success rates of setons and anti‐TNF for Crohn's perianal fistula. Method: Studies evaluating the effect of setons and anti‐TNF on Crohn's perianal fistula were included. Studies assessing perianal fistula in children, rectovaginal and rectourinary fistulae were excluded. The primary end‐point was the fistula closure rate. Partial closure and recurrence rates were secondary end‐points. Results: Ten studies on seton drainage were included ( n  =   305). Complete closure varied from 13.6% to 100% and recurrence from 0% to 83.3%. In 34 anti‐TNF studies ( n  =   1449), complete closure varied from 16.7% and 93% (partial closure 8.0–91.2%) and recurrence from 8.0% to 40.9%. Four randomized controlled trials ( n  =   1028) comparing anti‐TNF with placebo showed no significant difference in complete or partial closure in meta‐analysis (risk difference 0.12, 95% CI −0.06 to 0.30 and 0.09, 95% CI −0.23 to 0.41, respectively). Subgroup analysis ( n  =   241) showed a significant advantage for complete fistula closure with anti‐TNF in two trials with follow‐up > 4 weeks (46% vs 13%, P  =   0.003 and 30% vs 13%, P  =   0.03). Of four included cohort studies, two revealed a significant difference in response in favour of combined treatment ( P  =   0.001 and P  =   0.014). Conclusion: Closure and recurrence rates after seton drainage as well as anti‐TNF vary widely. Despite a large number of studies, no conclusions can be drawn regarding the preferred strategy. However, combination therapy with (temporary) seton drainage, immunomodulators and anti‐TNF may be beneficial in achieving perianal fistula closure.